1997
DOI: 10.1046/j.1365-2125.1997.00606.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of a selective muscarinic receptor antagonist and hyoscine (scopolamine) on motion sickness, skin conductance and heart rate

Abstract: Aims Hyoscine (scopolamine), which is effective in the prophylaxis of motion sickness, shows similar binding affinities to all of the five known muscarinic receptor sub-types. The effectiveness of hyoscine was compared with zamifenacin (UK-76654), which binds selectively to the muscarinic M 3 and m5 receptors. Methods Eighteen subjects received hyoscine hydrobromide 0.6 mg, zamifenacin 20 mg, or placebo (double-blind cross-over design). Sessions were 1 week apart and the drug (oral) was given 90 min prior to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
57
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 6 publications
13
57
0
Order By: Relevance
“…8) with intranasal and oral scopolamine, similar to findings reported by Golding and Stott (1997) using oral scopolamine, Klocker et al, (2001) using intranasal scopolamine and Parrott (1989) administering transdermal scopolamine. The heart rate data from this study indicate that 0.4 mg of intranasal scopolamine and 0.8 mg of oral scopolamine significantly decreased heart rate more than placebo over time, with differences being found at 75, 90, 115, and 165 minutes post intranasal dose and 165 minutes post oral scopolamine dose.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…8) with intranasal and oral scopolamine, similar to findings reported by Golding and Stott (1997) using oral scopolamine, Klocker et al, (2001) using intranasal scopolamine and Parrott (1989) administering transdermal scopolamine. The heart rate data from this study indicate that 0.4 mg of intranasal scopolamine and 0.8 mg of oral scopolamine significantly decreased heart rate more than placebo over time, with differences being found at 75, 90, 115, and 165 minutes post intranasal dose and 165 minutes post oral scopolamine dose.…”
Section: Discussionsupporting
confidence: 73%
“…A variety of pharmaceutical countermeasures have been tested for military and space environment application (i.e., anticholinergics, antihistamines, antimuscarinics, and CNS stimulants), with several decreasing the symptoms of motion sickness, but efficacy varies widely and detrimental performance side-effects are common (Cornum, Caldwell & Cornum, 1997;Cowings et al, 1996;Golding & Stott, 1997;Marcus & Furman, 2006;Putcha, 1999;Wood & Graybiel, 1968). The most widely used medication, and perhaps the most extensively researched, is the anticholinergic drug scopolamine.…”
Section: Scopolamine For Motion Sicknessmentioning
confidence: 99%
“…33 The connection of muscarinic acetylcholine receptor 3 subtype to PONV could be further reinforced by the nonspecific muscarinic receptor antagonists (e.g., scopolamine) being effective in the attenuation of motion sickness, a syndrome that seems to be closely related to PONV (i.e., previous history of either PONV or motion sickness are both major risk factors for PONV). 34,35 Previously published studies demonstrated that sequence variations in the promoter region of the CHRM3 gene may be associated with asthma, atopy, and early-onset type 2 diabetes. 36,37 The initial findings from the pooled assays were successfully replicated for only 4 of 24 SNPs in the validation cohort.…”
Section: Perioperative Medicinementioning
confidence: 99%
“…The phenomenon of increased EDA prior to syncope seems similar to sweating or EDA that commonly occurs with motion sickness [5,11,12]. As with NMS, EDA may precede symptoms of motion sickness.…”
Section: Discussionmentioning
confidence: 97%